Teleost skin microbiome: An intimate interplay between the environment and the host immunity - Wang, Liang-Chun; Chen, Li-Hsuan; Chiu, Yu-Che; Liou, Chung-Yi; Chen, Han-Chung; Lu, Chia-Yun; Chen, Jian-Lin (Fish & Shellfish Immunology, 2023)
The mucosal microbiome plays a role in regulating host health. The research conducted in humans and mice has governed and detailed the information on microbiome-host immunity interactions. Teleost fish, different from humans and mice, lives in and relies on the aquatic environment and is subjected to environmental variation. The growth of teleost mucosal microbiome studies, the majority in the gastrointestinal tract, has emphasized the essential role of the teleost microbiome in growth and health. However, research in the teleost external surface microbiome, as the skin microbiome, has just started. In this review, we examine the general findings in the colonization of the skin microbiome, how the skin microbiome is subjected to environmental change and the reciprocal regulation with the host immune system, and the current challenges that potential study models can address. The information collected from teleost skin microbiome-host immunity research would help future teleost culturing from the potential parasitic infestation and bacterial infection as foreseeing growing threats.